Development of Re-Usable Yeast-Gellan Gum Micro-Bioreactors for Potential Application in Continuous Fermentation to Produce Bio-Ethanol - Sook Mun Tan; Paul Wan Sia Heng; Lai Wah Chan (MDPI AG, 2011)
The objectives of this study were to investigate the feasibility of encapsulating yeast cells using gellan gum by an emulsification method and to evaluate the fermentation efficiency and the reusability of the micro-bioreactors produced. It was found that yeast cells could be successfully encapsulated to form relatively spherical micro-bioreactors with high specific surface area for mass transfer. Cell viability was found to be reduced by one log reduction after the emulsification process. The ethanol yield of the micro-bioreactors was comparable to that of free yeast in the first fermentation cycle. The micro-bioreactors remained intact and could be re-used up to 10 cycles of fermentation. Despite cell breakthrough, relatively high ethanol yields were obtained, indicating that the micro-bioreactors also functioned as regenerative reservoirs of yeast.